Isolation of carbazole alkaloids and coumarins from Aegle marmelos and Murraya koenigii and their antioxidant properties - Rou, Chian Ng; Nur Kartinee Kassim,; Soon, Yunie Yu Yeap; Cheng, Gwendoline Lian Ee; Saiful Latifah Yazan,; Khalid Hamid Musa, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this paper, antioxidant properties of Aegle marmelos (stem bark, leaves) and Murraya koenigii (stem bark, root) were evaluated by 2,2-diphenyl-1-picrylhydrazy (DPPH) free radical scavenging, 2,2’-Azino-bis(3-ethylbenzthiozoline-6-sulfonic acid) (ABTS) decolourisation, cupric reducing antioxidant capacity (CUPRAC), ferric reducing antioxidant power (FRAP) and linoleic acid/β-carotene assays. The chloroform extract of Murraya koenigii stem bark was found to possess the highest antioxidant activity in CUPRAC (1490.89 mgTE/g extract). In contrary, the hexane extract from Aegle marmelos leaves exhibited the weakest antioxidant activity in the DPPH assay (81.06 mgTE/g extract). The bioactive compound mahanimbine (7) isolated from the stem bark of Murraya koenigii was found to be the most active antioxidant agent with TEAC of 927.73 and 1649.31 mgTE/g corresponding to the ABTS and CUPRAC assays, respectively, as well as a good lipid peroxidation inhibitor with an inhibitory percentage of 70.95%. These CUPRAC and ABTS assays are the first report for Malaysian Murraya koenigii species.